Penrose limits of I-branes, twist-compactified D5-branes, and spin chains - Carlos Nunez (Physical Review D, 2024)
In this paper we consider the Penrose limit in the case of two gravity duals. One of them, consists of compactified I-branes [intersecting sets of D5-branes over (1+1) dimensions]. The second consists of D5-branes compactified on a circle. Both compactifications preserve supersymmetry. We find a match of the oscillators and masses of string modes on the resulting pp wave against a spin chain in a (2+1)-dimensional field theory in the first case, and a spin chain in a (1+1)-dimensional field theory in the second.